Pelatihan dan Pendampingan Penggunaan Aplikasi Sistem Upload Penerimaan dan Pengeluaran Dokumen (Suppermen) Berbasis Web di PT PUSRI Palembang - Eka Puji Agustini; Nyimas Sopiah; Muhammad Ariandi; Irman Effendy; Gege Ardiansyah; Hesti Sukmawati (Jurnal Nasional Pengabdian Masyarakat, 2022)
PT PUSRI Palembang is one of the State-Owned Enterprises (BUMN) companies that manage fertilizers in Indonesia. One of the activities in the financial division at PT PUSRI is collecting data on invoices and MPJP. Initially, this activity was still carried out manually which made it difficult for many vendors from outside the city